Establishment of an auxiliary virtual damping loop for the superior inertial response in the microgrid. Issue 1 (20th January 2020) - Bhowmik, Pritam; Rout, Pravat Kumar
Abstract : Low inertial microgrids in the power network are extremely sensitive toward any uncertainties. Therefore, the practise of complementing inertia virtually in microgrids has earned huge attention in recent time. However, the effect of inertia emulation virtually on the overall damping characteristics of the network has not been explored yet. Concerning to the fact, the study has put an effort to establish a decisive relationship between the inertial and damping powers. Furthermore, a trajectory analysis has been performed to acutely measure the individual effects of the virtual inertia and the virtual damping on the power network. On the basis of the observation from the trajectory analysis, the study has introduced the concept of the dynamic computation of virtual inertial constant by realising the novel self‐tuned proportional–integral‐based control mechanism. The study further has proposed the superimposed auxiliary dynamic virtual damping loop to suppress the frequency deflection time. To evaluate and justify the improvement of the system performance, the proposed integrated inertia‐damping emulation system has been relatively compared with the conventional virtual inertia emulation scheme in a microgrid testbed.